Towards energy benchmarking in residential buildings in the Kingdom of Saudi Arabia - Aladwani, Abdulaziz Mohammed (2025)
Countries worldwide are facing the challenges of improving energy efficiency and reducing carbon emissions to mitigate climate change, conserve resources, achieve energy security, and reap economic benefits. Over recent decades, the Kingdom of Saudi Arabia has experienced a rapid increase in domestic energy consumption. Notably, residential buildings have emerged as significant consumers, accounting for approximately 50% of the total electricity consumption within the building sector. This sustained expansion in energy demand raises concerns regarding environmental impact. Sustainability has recently become a fundamental issue in the Kingdom of Saudi Arabia (KSA), as one of the cornerstones of Saudi Vision 2030. One of the key initiatives under Vision 2030 is the Saudi Green Initiative, which aims to significantly reduce carbon emissions and achieve net zero emissions by 2060. To support the goals of the Saudi Green Initiative and promote sustainable growth, it is essential to develop effective strategies and tools for improving energy efficiency in residential buildings. One of the key challenges here is the lack of a national benchmark values that may help stakeholders to evaluate the energy consumption of their buildings. In response, this research attempts to develop a benchmarking framework tailored explicitly to the Saudi Arabian context and establish an energy benchmarking for residential buildings. The research is divided into five milestones. The first milestone involves a thorough review of energy consumption in the KSA, identifying factors contributing to energy demand, and reviewing the current energy benchmarking methods for buildings. This review provides a comprehensive insight into the energy consumption of residential buildings and identifies the most appropriate energy benchmarking methods, which can be adapted to the Saudi Arabian building context. The second research milestone involves collecting data from a representative sample of residential buildings in the Saudi Arabia. The third milestone involves improving the specifications of the representative sample buildings to comply with the Saudi Building Code (SBC) requirements. The fourth milestone concerns conducting statistical tests and analyses, which are necessary to ensure that the research is based on sound data and assumptions, contributing to the overall quality of the research. The last milestone involves developing energy benchmarks for villas and apartments in the KSA. The benchmark can contribute to improving building energy performance in the region. The benchmark provides insights into factors influencing energy use, enabling stakeholders to assess the energy efficiency of their buildings. The benchmark also educates the public about energy consumption patterns, influences building asset value, and aids policymakers in setting energy-efficiency standards and implementing incentives. The main findings reveal that applying the SBC-602/2018 requirements to the buildings can improve the energy consumption of villas and apartments by up to 19% and 40%, respectively. Moreover, the findings suggest that the normalised energy use intensity (EUInorm) benchmarks for villas and apartments that meet the SBC requirements in the Riyadh region are 60 kWh/m2/Yr and 98 kWh/m2/Yr, respectively. These benchmarking values were based on normalising the significant variables that affect energy consumption.